Monophasic Paravertebral Lumbar Synovial Sarcoma in an Adult Patient: Case Report - Santos, Bruno Amaral; Oliveira, Beatriz Segatto de; Antunes, Paulo Eduardo Hernandes; Santos, João Guilherme Carvalho de Oliveira; Prado, Eloy Theodoro José do; Menezes, Felipe Hammoud de; Menezes, Ellen Diniz de (Brazilian Journal of Case Reports, 2025)
Synovial sarcoma is a rare malignant soft-tissue tumor, accounting for about 8–10% of sarcomas and is frequently diagnosed in young adults. It most commonly arises in the lower limbs, with paravertebral location being uncommon. We report the case of a 46-year-old female patient with a progressively enlarging right lumbar mass, initially considered benign. Magnetic resonance imaging revealed a solid right paravertebral lesion with signs of aggressiveness. Biopsy confirmed a monophasic synovial sarcoma, grade 2 (WHO, 2022), with a mitotic index of 5 mitoses per 10 high-power fields and no necrosis. Staging was T2N0M0, stage IIIA. The patient underwent wide resection of the mass in the lumbar paravertebral musculature, with clear margins. She remains under clinical-oncologic follow-up and is being evaluated for adjuvant chemotherapy. This case highlights the importance of differential diagnosis in paravertebral tumors and reinforces the role of multidisciplinary management in the treatment of synovial sarcoma.